ANALYSIS OF THE INFLUENCE OF COMMUNITY ECONOMIC EMPOWERMENT AND FINANCIAL INCLUSION IN STRENGTHENING MSME CAPITAL (A STUDY OF GOVERNMENT PROGRAM LITERATURE IN INDONESIA) - Ahmad Rizani; Swanto Sirait; Pratiwi Subianto (Review of International Economy and Finance, 2025)
This study analyses the impact of community economic empowerment and financial inclusion on strengthening the capital of Micro, Small and Medium Enterprises (MSMEs) in Indonesia based on a literature review of various government programmes. The results show that synergistic efforts through training, business mentoring, and facilitating access to financing sources can significantly improve the capabilities and competitiveness of MSME actors. Financial inclusion programmes, such as People's Business Credit (KUR), business capital assistance, and financial service digitalisation, have proven to expand access to capital and boost business management efficiency. In addition, financial literacy and digital innovation further strengthen MSMEs' resilience to economic challenges and market changes. This study emphasises the importance of optimising the integration of community economic empowerment and financial inclusion through adaptive policies, regular monitoring, and ecosystem support to ensure that SME capital strengthening is effective, sustainable, and has a broad impact on the national economy.